49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3992
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigation of Transverse Combustion Instabilities

Abstract: Concurrent experiments and computations are used to analyze combustion instabilities in a transverse mode combustion chamber. The experiments employ a shear-coaxial injector element, positioned within a rectangular chamber and driven by high amplitude transverse acoustics modes by unstable injector elements located near the chamber end-walls. The reacting flow portion of the study element is optically accessible and the chamber is extensively instrumented with high-frequency pressure transducers. Different lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…It was found that the limit cycle does not produce shocks; upon grid refinement the pressure gradients in the transverse direction do not increase. This is consistent with the experimental findings of Shipley et al [17], which did not discover the existence of shocks in the experimentally measured instability. For the OOXOXOO case, a contour plot of the temperature field for the ethane injector is given in Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…It was found that the limit cycle does not produce shocks; upon grid refinement the pressure gradients in the transverse direction do not increase. This is consistent with the experimental findings of Shipley et al [17], which did not discover the existence of shocks in the experimentally measured instability. For the OOXOXOO case, a contour plot of the temperature field for the ethane injector is given in Fig.…”
Section: Resultssupporting
confidence: 91%
“…4. As can be seen on that plot, the maximum flame temperature is 2890 K, with a coflow temperature of 2660 K, which is in good agreement with the numerical results of Shipley et al [17], who report injector, at the outlet of one of the outermost driving injectors, at the center of the nozzle, and at the edge of the nozzle. The power spectrum density of the pressure signals is also shown, with peaks at the 1931 Hz frequency and its harmonics.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations